The Great Slave Lake PyroCb of 5 August 2014: Observations, Simulations, Comparisons With Regular Convection, and Impact on UTLS Water Vapor. Issue 21 (12th November 2018) - Kablick, G.; Fromm, M.; Miller, S.; Partain, P.; Peterson, D.; Lee, S.; Zhang, Y.; Lambert, A.; Li, Z.
Abstract: This study analyzes a pyrocumulonimbus (pyroCb) that formed near Great Slave Lake in the Northwest Territories of Canada on 5 August 2014 using multiple satellite‐ and ground‐based data sets, meteorological reanalysis, and a cloud‐resolving model. Passive and active polar‐orbiting instruments and geostationary imagery detail the intense updraft column during the several hours‐long convective stage and capture the entire pyroCb life cycle. CloudSat radar reflectivity profiles and local soundings show the pyroCb cloud base was ≥1 km above the lifting condensation level. Comparisons with profiles through meteorological convection in the same region reaffirm previous evidence for delayed droplet growth within pyroconvective updrafts. The pyroCb penetrated the tropopause, reaching at least 14 km (θ≃ 380 K), and the detrained cirrus/smoke plume was tracked over the following 2 weeks using lagrangian trajectories, the Cloud‐Aerosol Lidar with Orthogonal Polarization and Microwave Limb Sounder. Microwave Limb Sounder ice water content and water vapor mixing ratio (WVMR) observations in the aging plume show ice sublimation occurred in the stratosphere, producing individual WVMR anomalies up to +5 ppmv and plume‐averaged anomalies up to +2 ppmv. Reanalysis indicates the pyroCb formed in favorable convective conditions, but we show the fire itself triggered convection because meteorological triggers were not colocated during initiation. Cloud‐resolving model simulations confirm this result when controlled for surface fluxes, initial thermodynamics, and aerosol loading. Sensitivity tests show surface heat flux is dominant in determining overall pyroCb intensity, but aerosols and moisture inflow can effect small changes in updraft velocity, anvil ice concentration, and detrained WVMR. Key Points: Observations and simulations of a pyroCb show a distinct convective lifecycle from meteorological Cb A‐Train observations show ice sublimation in the aging plume over five days and enhanced localized water vapor in the stratosphere Model tests show pyroCb dynamics is dominated by surface heat flux, with lesser dependence on aerosol loading and midlevel instability.